Faktor Faktor yang Memengaruhi Use Behavior Pengguna Fintech Crowdfunding Melalui Behavioral Intention - Shuja Azmi Ismail; Ryna Parlyna; Osly Usman (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
The development of Fintech Crowdfunding in Indonesia has made it easier for people to conduct donations and social financing activities digitally. However, the level of continued use is still influenced by various psychological, social, and technological factors, especially among Generation Z as the largest digital user group. This study aims to analyze the influence of performance expectations, effort expectations, social influence, facilitating conditions, perceived risk, perceived trust, and hedonic motivation on behavioral intentions and their impact on the usage behavior of fintech crowdfunding users, with behavioral intentions as a mediating variable, on the Kitabisa platform. This study uses a quantitative approach with a survey method through a questionnaire to Generation Z users who have used the Kitabisa platform. The data analysis technique uses Structural Equation Modeling–Partial Least Squares (SEM-PLS) to test the direct and indirect relationships between variables. The results show that performance expectations, effort expectations, social influence, facilitating conditions, perceived trust, and hedonic motivation have a positive effect on behavioral intentions, while perceived risk has a negative effect on behavioral intentions. Furthermore, behavioral intentions are proven to have a positive and significant effect on usage behavior. The results of the mediation test indicate that behavioral intention is able to mediate the influence of all independent variables on usage behavior, both fully and partially. This finding suggests that fintech crowdfunding usage behavior is influenced not only by technological factors, but also by trust, risk perception, and user emotional motivation. Therefore, improving system quality, transparency, security, and user emotional experience are important factors in driving the desire to use fintech crowdfunding platforms.